Effect of spine biomechanical correction Kozyavkin's method (INRS) on components of muscle tone in children with spastic form of Cerebral Palsy and its possible prediction - V I Kozyavkin; N V Kozyavkina; O V Kozyavkina; М S Gordiyevych; V I Lysovych; Т B Voloshyn; І L Popovych; W Zukow (Kazimierz Wielki University, 2015)
Kozyavkin VI, Kozyavkina NV, Kozyavkina OV, Gordiyevych МS, Lysovych VI, Voloshyn ТB, Popovych ІL, Zukow W. Effect of spine biomechanical correction Kozyavkin's method (INRS) on components of muscle tone in children with spastic form of Cerebral Palsy and its possible prediction. Journal of Education, Health and Sport. 2015;5(1):11-30. ISSN 2391-8306. DOI: 10.13140/2.1.1035.0404 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A11-30 https://pbn.nauka.gov.pl/works/516604 http://dx.doi.org/10.13140/2.1.1035.0404   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. Conflict of interest: None declared. Received: 15.11.2014. Revised 05.12.2014. Accepted: 25.12.2014.   EFFECT OF SPINE BIOMECHANICAL CORRECTION KOZYAVKIN's METHOD (INRS) ON COMPONENTS OF MUSCLE TONE IN CHILDREN WITH SPASTIC FORM OF CEREBRAL PALSY AND ITS POSSIBLE PREDICTION   VI KOZYAVKIN, NV KOZYAVKINA, OV KOZYAVKINA, МS GORDIYEVYCH, VI LYSOVYCH, ТB VOLOSHYN, ІL POPOVYCH, W ZUKOW   International Clinic of Rehabilitation, Truskavets', Ukraine center@reha.lviv.ua Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl     Abstract   A clinical-physiological observations in 29 children aged 7÷16 years with spastic forms of cerebral palsy. State of Gross Motor Function was 1÷4 levels at GMFCS, the functional state of the hand (usually the left ) was 1÷4 levels at MACS, hand spasticity estimated in the range 0÷2 on a scale Åshworth (ASS). Neural component of muscle tone (N), registered device Neuroflexor, was in the range 0,48÷18,08, elastic component (E) ranging -1,80÷4,36, and its viscous component (V) ranging -0,80÷0,73. We found a strong correlation between N and ASS (r=0,74), GMFCS (r=0,66), MACS (r=0,66), whereas the correlation of these parameters E on the verge of significance (r=0,36; 0,32, 0,34), and V all with their not related (r=0,14; 0,00; -0,15). After 10-15 min after the first spine biomechanical correction Kozyavkin' method N in 17 children decreased from 7,6±1,1 by 3,4±0,7 (p<0,001), in 4 children has not significantly changed: 2,9±1,7 to and 2,5±1,6 after correction, and in 8 cases increased from 5,8±2,1 by 2,2±0,7 (p<0,01). After a two-week course of rehabilitation by Kozyavkin's method reducing N stated in 23 (79,3%) children from 7,6±1,0 by 6,0±0,8 (p<0,001). In 4 (13,8%) children changes were not detected: 1,6±0,6 to and 2,0±0,7 after treatment, however, in 2 cases N increased from 1,6 to 3,4 and from 4,6 to 6,1. Multiple regression equation to calculate the expected value of N as after the first correction of the spine, and after a two-week course of rehabilitation Kozyavkin's method. The method of discriminant analysis revealed that the nature of emergency response N at correcting the spine is projected for a range of initial parameters to within 72,4% and accuracy of predictions on the nature of the reaction of N treatment is 93,1%.   Keywords: cerebral palsy, neural, elastic and viscous components of muscle tone, Intensive Neurophysiological Rehabilitation by Kozyavkin, prediction.